Marketing's and Operations' Roles in Product Recall Prevention: Antecedents and Consequences - Chakravarty, Anindita; Saboo, Alok R.; Xiong, Guiyang (Production and Operations Management, 2022)
This study centers on the roles of marketing and operations capabilities in preventing future recalls. However, prior literature identifies operations capability as critical for recall prevention, the current research highlights the equivalent importance of marketing capability. Furthermore, rather than limiting marketing's role to damage control efforts after a recall, this study identifies its potential for preventing future recall incidents. With research conducted in the consumer packaged goods industry, the authors determine that firms that improve their marketing and operations capabilities after a recall lower their likelihood of future recalls. A proposed motivation‐based model for post‐recall marketing and operations capability improvement predicts that recalling public firms, by default, do not invest in capability improvements. The test of the propositions, with a sample of 276 product recalls using joint estimation, reveals that stock market penalties for recalls, combined with analyst following and independent boards, push recalling firms to make capability improvements. However, well‐reputed firms and those whose competitors recently engaged in recalls push back against investors' demands.